Hysterosalpingoscintigraphy: A Simple and Accurate Method of Evaluating Fallopian Tube Patency - Becker, W.; Steck, T.; Albert, P.; Börner, W. (Nuklearmedizin - NuclearMedicine, 1988)
A prospective study was designed to evaluate the efficacy of radionuclide hysterosalpingoscintigraphy using 99mTc-labelled human serum albumin macroaggregates in 17 patients (34 tubes). In normal females the niacroaggregates migrate spontaneously through the female reproductive tract following application into the posterior vaginal fornix. They can be seen in the uterine fornix 20 min p. i. (range: 5-90 min) and as free pelvic activity 120 min p. i. (range 40-180 min). Free pelvic activity could also be demonstrated by culdocentesis. In infertile patients with failure of tubal patency images after 180 min offered no additional information. For the routine diagnosis camera images 5, 60 and 180 min p. i. are recommended. Using 5-10 MBq 99mTc the radiation exposure to the ovaries is about 1/9th of the exposure from a normal radiologic hysterosalpingogram. The reported data show results comparable with those of hysterosalpingography (HSG) in females with patent or with nonpermeable tubes, but in cases of high-pressure patency by HSG the results of scintigraphy are superior to those of HSG. Moreover, this method provides new insights into sperm motility under various physiological and pathological conditions.